APPROACH TO FACIAL TRAUMA IN POLYTRAUMATIZED PATIENTS (International Seven Journal of Multidisciplinary, 2025)
Facial trauma in polytraumatized patients is a highly complex condition that requires a robust interdisciplinary approach, frequently associated with traffic accidents and high-energy injuries. This narrative review analyzes current management strategies, emphasizing the prioritization of hemodynamic stabilization and airway maintenance according to Advanced Trauma Life Support (ATLS) protocols, often postponing definitive facial treatment under the Damage Control doctrine. The findings indicate the superiority of surgical intervention with rigid osteosynthesis over conservative treatment in reducing functional and aesthetic sequelae, such as malocclusion and asymmetry. The study discusses specific challenges, such as the management of fractures in atrophic mandibles (which may require bone grafting according to the Luhr classification) and the need for immediate microsurgical replantation in cases of traumatic amputations.